Pathophysiology and possible treatments for olfactory-gustatory disorders in patients affected by COVID-19 - Francisca Idalina Neta; Amélia Carolina Lopes Fernandes; Adson José Martins Vale; Francisco Irochima Pinheiro; Ricardo Ney Cobucci; Eduardo Pereira de Azevedo; Fausto Pierdoná Guzen (Elsevier, 2021)
SARS-CoV-2 infects host cells mainly through the interaction between the virus's Spike protein and the viral receptors namely Angiotensin-Converting Enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2). Both are highly expressed in the gastrointestinal tract, in the nasal and bronchial epithelium, as well as in the type II alveolar epithelial cells. The aim of this review is to report the evidences from the scientific literature on the pathophysiology and the available treatments for olfactory-gustatory disorders in patients with COVID-19. The mechanisms involved in these disorders are still unclear and studies on specific therapies are scarce. However, it has been hypothesized that a decrease in the sensitivity of the sensory neurons as well as the co-expression of ACE2 and TMPRSS2 in the alveolar epithelial cells are the main causes of olfactory-gustatory disorders. The possible mechanisms described in the literature for changes in taste perception in patients with COVID-19 include olfactory disorders and a competitive activity of COVID-19 on ACE2 receptors in the taste buds. In addition, SARS-CoV-2 can bind to sialic acid receptors in the taste buds. In general, evidences show that there is no specific treatment for olfactory-taste disorders induced by SARS-CoV-2, even though some treatments have been used and have shown some promising results, such as olfactory training, intranasal application of sodium citrate and vitamin A, as well as systemic use of omega-3 and zinc. Corticosteroids have also been used as a pharmacological approach to treat patients with olfactory dysfunction with some contradictory results. The knowledge of the mechanisms by which SARS-CoV-2 influences the sensory systems and how effective therapies can treat the loss of smell and taste will have important implications on the understanding and clinical management of olfactory-taste disorders.